2009
DOI: 10.1039/b900443b
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the hydrolytic stability of 2′-fluoroarabinonucleic acid (2′F-ANA)

Abstract: The stability of 2'-deoxy-2'-fluoroarabinonucleic acid (2'F-ANA) to hydrolysis under acidic and basic conditions was compared to that of DNA, RNA and 2'F-RNA. In enzyme-free simulated gastric fluid (pH approximately 1.2), 2'F-ANA was found to have dramatically increased stability (virtually no cleavage observed after 2 days) with respect to both DNA (t(1/2) approximately 2 min) and RNA (t(1/2) approximately 3 h (PO) or 3 days (PS)). These results were observed for both phosphodiester and phosphorothioate backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…4´-Fluoro nucleosides are relatively unexplored in the literature, investigated in only a handful of studies (36)(37)(38)(39)(40), most of which encountered acid instability of the glycosidic linkage, which precluded these molecules from further studies and incorporation within oligonucleotides. We showed that the 2´,4´-difluoro ribo (34) and arabino (35) nucleosides had enhanced acid stability owing to the presence of the 2´-fluorine (41). Furthermore, we showed that the electronegative 4´ fluorine reinforced the RNA-like (3´-endo) conformation of 2´-F-ribonucleosides through an additional anomeric effect (F4´-C4´-O4´).…”
Section: Introductionmentioning
confidence: 89%
“…4´-Fluoro nucleosides are relatively unexplored in the literature, investigated in only a handful of studies (36)(37)(38)(39)(40), most of which encountered acid instability of the glycosidic linkage, which precluded these molecules from further studies and incorporation within oligonucleotides. We showed that the 2´,4´-difluoro ribo (34) and arabino (35) nucleosides had enhanced acid stability owing to the presence of the 2´-fluorine (41). Furthermore, we showed that the electronegative 4´ fluorine reinforced the RNA-like (3´-endo) conformation of 2´-F-ribonucleosides through an additional anomeric effect (F4´-C4´-O4´).…”
Section: Introductionmentioning
confidence: 89%
“…Nevertheless, while the gymnotic activity of the LNA gapmers is high and extremely robust in tissue culture, it is uncertain whether these molecules are uniquely competent. Damha and co-workers 10,11,12,13,14,15 have synthesized antisense oligos that substitute 2′-deoxy, 2′-fluoro-β- D -arabinonucleic acid (2′F-ANA: arabinose is an epimer of ribose at C2′) for deoxyribose in the oligo chain. Because the 2′-fluorine atom does not significantly perturb duplex helix structure, phosphorothioate 2′F-ANA/RNA duplexes activate RNase H. 12,13 Furthermore, this ability may even be greater for 2′F-ANA/DNA phosphorothioate chimeras than for the corresponding deoxyribose phosphorothioate oligos.…”
Section: Introductionmentioning
confidence: 99%
“…The masses determined for peaks 4 through 7, which are poorly resolved, and 9 and 10, which are poorly resolved from the sense strand peak, correspond to the mass of the sense strand that has undergone loss of one adenine (observed: 117.1; calculated: 117.1) or one guanine (observed: 133.4; calculated: 133.1). All of these degradants can be formed through a mechanism involving an oxocarbonium ion intermediate (Watts et al, 2009) and this reaction generally leads to strand scission. Figure 11 (adapted from Watts and Burrows) illustrates the loss of adenine from a segment of DNA, yielding a product with the mass of the full-length DNA segment minus 117.1 amu corresponding to one of the masses observed in this experiment.…”
Section: 01m Hcl Solution Samplementioning
confidence: 99%